Be the best bad presenter ever : break the rules, make mistakes, and win them over - Hough, Karen; Safari eBooks ([Place of publication not identified] : Berrett-Koehler Publishers, 2015)
"Many people find public speaking can be scary, but it doesn't need to be. In this course, you'll toss out the old "tried-and-true" rules of presentation and in the process transform yourself into a confident, authentic presenter. Former network engineering executive and stage actor Karen Hough uses wit and wisdom to show you how "being bad" at public speaking can really work. Discover the true purpose of any presentation (hint: it's not to convey information). Learn the value of emotions in public speaking--even nervousness and fear. Understand why your voice is more important than your slides. Nail the most critical parts of any presentation: the bookends. Learn how to practice a speech (hint: break your mirror). Know how to read--and not read--an audience. Get tips for what to do when something goes wrong. Yale graduate Karen Hough teaches public speaking as founder and CEO of ImprovEdge. She is the recipient of the Athena PowerLink Award for outstanding women-owned businesses and is a national conference keynote speaker on topics such as executive presence and presentation skills, negotiation, and leadership."--Resource description page.
Title from title screen (viewed December 3, 2015).
On-screen presenter, Karen Hough.
Keywords: Business presentations; Public speaking; Business communication; Electronic books